2009
DOI: 10.1021/jp904107x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Photon-to-Carrier Efficiencies of Alternating Nanolayers of Zinc Phthalocyanine and C60 Films Assessed by Time-Resolved Terahertz Spectroscopy

Abstract: Multilayer and 1:1 blended films of zinc phthalocyanine (ZnPc) and buckminsterfullerene (C 60 ) were investigated as model active layers for solar cells by time-resolved terahertz spectroscopy (TRTS). Relative photon-to-carrier efficiencies were determined from ultrafast decay dynamics of photogenerated carriers using 400 and 800 nm excitation for delay times up to 0.5 ns. The findings are in good agreement with reported solar-cell device measurements, and the results exhibit a near linear increase of the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…It is clear that, given our current state of understanding of THz spectroscopy to these types of systems, future applications of time-resolved terahertz spectroscopy can focus on systems of increasing complexity, such as those encountered in photovoltaic devices where different semiconductor phases are intermixed on nanometer lengths scales (Esenturk et al, 2009). Such complex systems may include, for instance, semiconductor nanostructures (quantum dots or nanorods) embedded in an organic polymer semiconductor phase and quantum dot or dye-sensitized transition metal oxide systems (Tiwana et al, 2009;Nemec, Rochford et al, 2010;Pijpers et al, 2010Pijpers et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that, given our current state of understanding of THz spectroscopy to these types of systems, future applications of time-resolved terahertz spectroscopy can focus on systems of increasing complexity, such as those encountered in photovoltaic devices where different semiconductor phases are intermixed on nanometer lengths scales (Esenturk et al, 2009). Such complex systems may include, for instance, semiconductor nanostructures (quantum dots or nanorods) embedded in an organic polymer semiconductor phase and quantum dot or dye-sensitized transition metal oxide systems (Tiwana et al, 2009;Nemec, Rochford et al, 2010;Pijpers et al, 2010Pijpers et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrafast optical and terahertz studies of polymer blend and multilayer photovoltaic systems have probed charge separation processes into the subpicosecond regime, [3][4][5] producing much useful insight. For instance, recent work has highlighted the potential impact of bound interfacial chargetransfer ͑ICT͒ states on charge separation.…”
mentioning
confidence: 99%
“…In each case these curves can be fit to a bi-exponential decay (see Table 2). Our TRTS measurements have shown that the long-lived component decays on a time scale that approaches nanoseconds [4], and is assigned to quasi-free photocarriers. These carriers are of technological interest since they represent photoconversion efficiency.…”
Section: Resultsmentioning
confidence: 77%
“…Using TRTS, the electrical properties of the organic thin films are determined using spectroscopy, which eliminates the need to make "ohmic" contacts with the organic material. TRTS has been applied recently to a variety of organic materials [4,5]. background pressure of 10 -6 Torr at a rate of 0.5 -1 Å /second.…”
Section: Introductionmentioning
confidence: 99%